EVALUASI PELAKSANAAN KETERAMPILAN 4C (CREATIVE THINKING, CRITICAL THINKING AND PROBLEM SOLVING, COMMUNICATION, AND COLLABORATION) DI SMK KOMPETENSI KEAHLIAN OTKP KOTA SURABAYA - Fitriana Rahmawati; Brillian Rosy; Lifa Farida Panduwinata; Farhat Haque (Jurnal Pendidikan Ilmu Sosial, 2023)
The 4C skills (Creative Thinking, Critical Thinking, Problem-Solving, Communication, and Collaboration) are needed in the 21st century to support learning and prepare students to compete in the labour market. This study aims to determine the implementation of 4C skills in productive subjects of competency skills for Vocational High Schools (SMK) Otomatisasi dan Tata Kelola Perkantoran (OTKP) in 17 schools in Surabaya City. This evaluation research uses the CIPP method (Context, Input, Process, Product). The method used is a combination method (Mix Methods). The results showed that the suitability of applying the 4C skills at the Surabaya City OTKP Skills Competency Vocational School for each aspect of context, input, process, and product was in the high category. In addition, from the results of documentation and observation in the learning process, the teacher has carried out the four aspects of 4C skills. It can be concluded that the application of 4C skills has been going well.